2015
DOI: 10.4103/0975-7406.155764
|View full text |Cite
|
Sign up to set email alerts
|

Health problems and stress in Information Technology and Business Process Outsourcing employees

Abstract: Stress is high in software profession because of their nature of work, target, achievements, night shift, over work load. 1. To study the demographic profile of the employees. 2. To access the level of job stress and quality of life of the respondents. 3. To study in detail the health problems of the employees. All employees working in IT and BPO industry for more than two years were included into the study. A detailed questionnaire of around 1000 IT and BPO employees including their personal details, stress s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 19 publications
4
50
0
6
Order By: Relevance
“…It was also agreed by previous researcher in their finding. 2,6 Health problems such as visual, musculoskeletal and stress problems were observed. Related to visual problems pain, irritation, redness of eye and blurring of vision was seen in most of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was also agreed by previous researcher in their finding. 2,6 Health problems such as visual, musculoskeletal and stress problems were observed. Related to visual problems pain, irritation, redness of eye and blurring of vision was seen in most of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 76% of Computer professionals from India reported musculoskeletal discomfort in various epidemiological studies (Talwar et al, 2009;Bhanderi ISSN : 0974-9411 al., 2007;Sharma et al, 2006, Bakhtiar et al, 2003. Padma et al (2015) in a study on information technology employees also found that around 56 % had musculoskeletal symptoms, 54% had depression, anxiety, insomnia and 22% had newly diagnosed hypertension. In the absence of a good ergonomic design, extended work for prolonged periods can adversely affect vision, muscles of the neck, upper back, shoulders and arms, leading to visual and muscular fatigue and discomfort (musculoskeletal condition).…”
Section: Introductionmentioning
confidence: 97%
“…The demographic variety which is unique to the country has added another dimension to the study of the cultural and behavioural impacts of these sudden changes. The employees in the Indian IT/BPO sector have been experiencing a number of mental health issues, especially stress-related problems [7]. This is one job sector which has seen a spurt of growth in the recent decades.…”
Section: The Indian Scenariomentioning
confidence: 99%
“…The association between workplaces and stress is not a topic of academic interest anymore. Even newspapers or popular media in India are discussing the same on a regular basis, along with academic research inputs [7]; [8]; [9]; [39].…”
Section: Occupational Mental Health: An Overviewmentioning
confidence: 99%